Nilai-nilai kearifan lokal wayang topeng malangan sebagai sumber pembelajaran sejarah - Mahfud, Muhammad Hasmal; Wahyudi, Deny Yudo (Historiography: Journal of Indonesian History and Education, 2023)
Local wisdom is considered a solution to the nation's moral problems, which have been eroded by the negative side of globalism. Wayang Topeng Malangan is one of Malang's unique local wisdoms and has potential as a source of learning history, especially in Malang. The goal of this research was to look into local values in Malangan Mask Wayang art to use as a source for learning history in school. This research method uses qualitative methods and data collection through literature and interviews. The result is that the local wisdom of Wayang Topeng Malangan contains values in the form of religious values, moral values, and aesthetic values. The use of the Malangan Mask Puppet as a source for learning history in class can be used as an apperception for learning Hindu-Buddhist history in phase E or grade 10 high school in the form of apperception photos, pictures, and apperception videos and texts.Kearifan lokal dinilai sebagai solusi bagi permasalahan moral bangsa yang tergerus sisi negatif globalisme. Wayang Topeng Malangan salah satu kearifan lokal khas Malang dengan potensi sebagai sumber belajar sejarah khususnya di Malang. Tujuan penelitian ini untuk menggali nilai-nilai lokal dalam kesenian Wayang Topeng Malangan untuk digunakan sebagai sumber belajar sejarah di kelas. Metode penelitian ini menggunakan metode kualitatif dan pengumpulan data dengan kepustakaan dan wawancara. Hasilnya kearifan lokal Wayang Topeng Malangan mengandung nilai-nilai berupa nilai religius, nilai moral, dan nilai estetika. Penggunaan Wayang Topeng Malangan sebagai sumber belajar sejarah dikelas dapat digunakan sebagai apersepsi pembelajaran sejarah Hindu Budha di fase E atau kelas 10 SMA berupa apersepsi foto atau gambar dan apersepsi video dan naskah.